Penerapan Metode EOQ dan ROP untuk Pengembangan Sistem Informasi Inventory Bengkel MJM berbasis Web - Trian Rafliana; Bernard Renaldy Suteja (Maranatha University Press, 2018)
MJM is a small company that works in the automotive business especially for a two-wheeled vehicle. Nowadays MJM has already using the information system to make the listings for the items, sales, and procurement. When the stock is getting low, MJM orders the item to the supplier but sometimes it’s not optimal because the amount of the items they bought are always too much or too less than the needs, and sometimes they ordered the items on the wrong time. The goal here is to make the owner of the shop able to analyze the optimal amount of items when ordering using the EOQ (Economic Order Quantity) method and to analyze when is the right time to reorder the items using ROP (ReOrder Point), so in the future this application will be useful for the owner.